A Database-based Automatic Cartography Method - T. Zhao; T. Zhao; Y. Peng; Y. Peng; W. Liu; W. Liu; W. Ma; X. Di; Z. Cai; X. Wang; X. Wang; L. Che (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
At present, GIS data, which contains a large amount of semantic information, has become the main data source for map cartography. In this paper, based on the existing multi-scale database, we study a database-based automatic cartography method to meet the needs of multi-scale map cartography, and replace the traditional process by the intelligent processing of software to shorten the cycle of cartography, improve the productivity of map cartography, and at the same time, reduce the error rate caused by manual work, and improve the overall quality of map production.